2022
DOI: 10.3389/fimmu.2022.977358
|View full text |Cite
|
Sign up to set email alerts
|

Explainable artificial intelligence for precision medicine in acute myeloid leukemia

Abstract: Artificial intelligence (AI) can unveil novel personalized treatments based on drug screening and whole-exome sequencing experiments (WES). However, the concept of “black box” in AI limits the potential of this approach to be translated into the clinical practice. In contrast, explainable AI (XAI) focuses on making AI results understandable to humans. Here, we present a novel XAI method -called multi-dimensional module optimization (MOM)- that associates drug screening with genetic events, while guaranteeing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…48 Therefore, by adding the XAI technology to ML and DL models, the use of AI in healthcare will become more reliable and acceptable. [49][50][51] In addition, before application, the public should be educated on the principles of the medical AI system, including how it works.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Therefore, by adding the XAI technology to ML and DL models, the use of AI in healthcare will become more reliable and acceptable. [49][50][51] In addition, before application, the public should be educated on the principles of the medical AI system, including how it works.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study involving categorising tuberculosis diagnoses through deep learning chest radiographs, researchers used heat maps to show areas of increased activation of deep learning networks that could be inferred to be important for diagnosis 48. Therefore, by adding the XAI technology to ML and DL models, the use of AI in healthcare will become more reliable and acceptable 49–51. In addition, before application, the public should be educated on the principles of the medical AI system, including how it works.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to use the majority of commercially available cell lines because of the lack of this specific alteration in the majority of them. ME-1 cell line is a unique exception [ 116 ].…”
Section: Aml Cell Lines and Typesmentioning
confidence: 99%
“…They found that they successfully validated their results in three large-scale screening experiments. In this way, they have proven that XAI will help healthcare providers and drug regulators better understand AI medical decisions (Gimeno et al, 2022). It has been shown that machine learning models and scoring functions that simplify the screened Coulomb and Lennard-Jones interactions between ligands and residues of the target receptor can significantly improve the classification ability to improve the mentioned virtual screening and identify active ligands (Shimazaki & Tachikawa, 2022).…”
Section: Uncertainty Estimationmentioning
confidence: 99%